ANALISIS PENGARUH IKLIM ORGANISASI, KOMUNIKASI ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP DISIPLIN KERJA (Studi Pada Karyawan Divisi Operasional PT. Plasa Simpanglima Semarang) - Hermaya, Zhara M.; Yuniawan, Ahyar (Diponegoro Journal of Management, 2018)
This study aims to examine and analyze the influence between organizational climate, organizational communication and organizational commitment to work discipline. In this study, researchers studied the work discipline of the Operational Division of PT. Plasa Simpanglima Semarang by using independent variable that is organization climate, organizational communication and organizational commitment, and dependent variable that is work discipline.This study was conducted through the distribution of questionnaires to employees by using the census method as much as 110 people. Data analysis method used is multiple linear regression analysis. Where the test data used include validity test, reliability test, classical assumption test, t test, F test, coefficient of determination (Â and multiple linear regression analysis.Based on the research results shows that organizational climate have positive and significant effect to work discipline. Organizational communication has a positive andsignificant impact on work discipline. Finally, organizational commitment has a positive and significant impact on work discipline. Coefficient of determination indicates that work discipline is influenced by organizational climate, organizational communication and organizational commitment equal to 68,9% while the rest of 31,1% influenced by other variables not examined in this research.